Methods to Improve Water Quality and Their Relevance: Enhancing Water Quality through Bokashi Ball Treatment (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Water is a vital part of our lives. No one will live without water for a longer periods. Water quality is also significant, as polluted water will rise among living organisms to many diseases. Therefore different approaches are used to improve the water quality. In certain situations, the water is filtered using successful micro-organism methods. That technology should be environmentally sustainable. This approach was used to increase the consistency of the water in different rivers.It is found that the level of water quality is declining year by year with the rise in population. Hence, there is a growing need to improve water safety. In this paper we highlight treatment of Bokashi ball to enhance water quality.